Non-state certification of smallholders for sustainable palm oil in Sumatra, Indonesia - Apriani, E.; Kim, Y.S.; Fisher, L.A.; Baral, H. (Elsevier, 2020)
Rapid expansion of oil palm plantations is one of the leading causes of Indonesia's continued deforestation over the past decades. To reverse this trend against the wave of increasing global demand for palm oil, non-state certification programs, such as the Roundtable on Sustainable Palm Oil (RSPO), have been promoted to ensure sustainable palm oil production. However, limited empirical studies exist for understanding how RSPO is perceived and practiced by various stakeholders along the palm oil supply chain, especially at the source by small-scale farmers. We surveyed 181 certified independent smallholders in two sites in Jambi, Sumatra to understand: (1) the challenges and benefits of participating in RSPO; (2) the willingness of independent smallholders to continue their participation; and 3) the factors affecting their willingness. We found that most of the challenges of RSPO certification are not well understood by smallholders, except the need for organizational support. In both sites, extensive external support from a local NGO was the key factor that facilitated RSPO certification. Most of the respondents recognize both non-financial (e.g. knowledge, market access, and social recognition) and financial benefits (e.g. sales from RSPO credits) of certification. Although overall, direct financial benefits may be small, they can be a motivator for farmers to continue with certification and for others to consider joining the group when disbursed equitably in non-monetary and communal form, such as in shared food. In contrast, indirect and long-term benefits were not enough to motivate smallholders to maintain RSPO certification. This study provides important insights about the characteristics of the leaders (governing members) and factors affecting RSPO participation from actual experiences of certified smallholders. The information can be used to target early adopters to initiate the RSPO process in farmers' groups and to develop appropriate facilitation strategies at different stages of certification development for independent smallholders.